Grazing lowers soil multifunctionality but boosts soil microbial network complexity and stability in a subtropical grassland of China - Ding, Leilei; Tian, Lili; Li, Jingyi; Zhang, Yujun; Wang, Mengya; Wang, Puchang (Frontiers in Microbiology, 2023)
Long term-grazing profoundly affects grassland ecosystems, whereas how the soil microbiome and multiple soil ecosystem functions alter in response to two-decade grazing, especially how soil microbiome (diversity, composition, network complexity and stability) forms soil multifunctionality, are rarely addressed. We used a long-term buffalo grazing grassland to measure the responses of soil physicochemical attributes, stoichiometry, enzyme activities, soil microbial niche width, structure, functions, and networks to grazing in a subtropical grassland of Guizhou Plateau, China. The evidences from this work suggested that grazing elevated the soil hardness, available calcium content, and available magnesium content by 6.5, 1.9, and 1.9 times (p = 0.00015 – 0.0160), acid phosphatase activity, bulk density, pH by 59%, 8%, and 0.5 unit (p = 0.0014 – 0.0370), but decreased the soil water content, available phosphorus content and multifunctionality by 47%, 73% and 9% – 21% (p = 0.0250 – 0.0460), respectively. Grazing intensified the soil microbial carbon limitation (+78%, p = 0.0260) as indicated by the increased investment in the soil β-glucosidase activity (+90%, p = 0.0120). Grazing enhanced the complexity and stability of the bacterial and fungal networks but reduced the bacterial Simpson diversity (p < 0.05). The bacterial diversity, network complexity and stability had positive effects, while bacterial and fungal compositions had negative effects on multifunctionality. This work is an original attempt to show that grazing lowered multifunctionality via the reduced bacterial diversity and shifted soil bacterial and fungal compositions rather than the enhanced bacterial and fungal network complexity and stability by grazing. Protecting the bacterial diversity from decreasing, optimizing the composition of bacteria and fungi, and enhancing the complexity and stability of bacterial network may be conducive to improving the soil multifunction of grazing grassland, on a subtropical grassland.